Interactive Digital Media to Enhance Early Literacy in Hybrid Learning - Kristin Anggraini; Nurlaiha Ibrahim; Nia Jusniani; Agustinus Prasetyo (LP. Ma'arif Janggan Magetan, 2025)
The development of hybrid learning models that are increasingly widespread, especially after the COVID-19 pandemic, has transformed early childhood education and created a demand for innovative approaches in early literacy development. This study examines the effectiveness of interactive digital media in improving the literacy skills of children aged 4–6 years within the hybrid learning context. Using a mixed-method design, quantitative measurement of literacy achievement was combined with qualitative observations and interviews involving educators and parents in several early childhood education institutions. The results demonstrate that interactive digital media significantly enhances basic literacy competencies, such as phonemic awareness, vocabulary enrichment, and storytelling skills, when effectively integrated with traditional learning methods. Novelty lies in the integration of early literacy development, digital media, and hybrid learning, which has rarely been explored in the Indonesian context. Factors determining effectiveness include media usability, content relevance, parental involvement, and the facilitator role of educators. These findings contribute empirical insights to optimize the use of interactive technology in early childhood hybrid learning environments. Practical implications emphasize the importance of designing digital content that is age-appropriate, culturally sensitive, and engaging, as well as strengthening hybrid learning frameworks to support literacy development as a foundation for lifelong learning succes.